Inter-Observer and Intra-Observer Variability in Gross Tumor Volume Delineation of Primary Esophageal Carcinomas Based on Different Combinations of Diagnostic Multimodal Images - Li, Fengxiang; Li, Yankang; Wang, Xue; Zhang, Yingjie; Liu, Xijun; Liu, Shanshan; Wang, Wei; Wang, Jinzhi; Guo, Yanluan; Xu, Min; Li, Jianbin (Frontiers in Oncology, 2022)
Background and Purpose This study aimed to investigate inter-/intra-observer delineation variability in GTVs of primary esophageal carcinomas (ECs) based on planning CT with reference to different combinations of diagnostic multimodal images from endoscopy/EUS, esophagography and FDG-PET/CT. Materials and Methods Fifty patients with pathologically proven thoracic EC who underwent diagnostic multimodal images before concurrent chemoradiotherapy were enrolled. Five radiation oncologist independently delineated the GTVs based on planning CT only (GTVC), CT combined with endoscopy/EUS (GTVCE), CT combined with endoscopy/EUS and esophagography (X-ray) (GTVCEX), and CT combined with endoscopy/EUS, esophagography, and FDG-PET/CT (GTVCEXP). The intra-/inter-observer variability in the volume, longitudinal length, generalized CI (CIgen), and position of the GTVs were assessed. Results The intra-/inter-observer variability in the volume and longitudinal length of the GTVs showed no significant differences (p>0.05). The mean intra-observer CIgen values for all observers was 0.73 ± 0.15. The mean inter-observer CIgen values for the four multimodal image combinations was 0.67 ± 0.11. The inter-observer CIgen for the four combined images was the largest, showing significant differences with those for the other three combinations. The intra-observer CIgen among different observers and inter-observer CIgen among different combinations of multimodal images showed significant differences (p<0.001). The intra-observer CIgen for the senior radiotherapists was larger than that for the junior radiotherapists (p<0.001). Conclusion For radiation oncologists with advanced medical imaging training and clinical experience, using diagnostic multimodal images from endoscopy/EUS, esophagography, and FDG-PET/CT could reduce the intra-/inter-observer variability and increase the accuracy of target delineation in primary esophageal carcinomas.